LYING FLAT IN MALAYSIA: UNDERSTANDING TANG PING AMONG CHINESE MALAYSIAN YOUTHS AS COUNTERCULTURE, DEFEATISM, AND SMART INDIVIDUALISM - Lee , Jenn Yuan; Chin , Yee Mun; Yong , Xin Yi (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
This study investigates the emergence of tǎng píng (躺平, “lying flat”) among Chinese Malaysian youths as a cultural repertoire of adaptation and resistance in late modernity. While the concept originated in mainland China as a critique of overwork and hyper-competition, its meanings and resonance in Malaysia remain underexplored. Drawing on survey data from 367 Chinese Malaysian respondents aged 16–30, this study examines awareness, interpretive frames, and domain-specific orientations toward tǎng píng. Findings reveal that although fewer than 10% of respondents explicitly identify with tǎng píng, more than half occupy ambivalent positions, treating it as a potential strategy rather than a fixed identity. Gendered differences are evident: women tend to associate tǎng píng with pressures surrounding marriage and family, while men more often connect it to workplace frustrations. Peer networks and social media emerge as the strongest influences, surpassing family or traditional institutions. Theoretically, the study situates tǎng píng along three interrelated axes—counterculture, defeatism, and smart individualism—arguing that it operates less as an organized movement than as a diffuse cultural repertoire of selective disengagement. By contextualizing tǎng píng within Malaysian diasporic dynamics, this research highlights how global youth idioms are localized, negotiated, and hybridized in response to structural precarity, intergenerational expectations, and digital circulation.